Climbing up Ladders and Sliding down Snakes: An Empirical Assessment of the Effect of Social Mobility on Subjective Wellbeing - Paul Dolan; Grace Lordan (Institute of Labor Economics (IZA), 2019)
We examine how intergenerational mobility affects subjective wellbeing (SWB) using data from the British Cohort Study. Our SWB measures encapsulates both life satisfaction and mental health, and we consider both relative and absolute movements in income. We find that relative income mobility is a significant predictor of life satisfaction and mental health, whether people move upward or downward. For absolute income, mobility is only a consistent predictor of SWB and mental health outcomes if the person moves downwards, and in this case the impact is far larger than relative mobility. For both relative and income mobility downward movements affect SWB to a greater extent than upward movements, consistent with notions of loss aversion. Notably, we find that social class mobility does not affect SWB. We present evidence that the significant relative and absolute mobility effects we find operate partially through financial perceptions and consumption changes which can occur because of income mobility.
Keywords: D31; D63; I1; J60; 330; income mobility; relative income; social class mobility; loss aversion; intergenerational mobility; life satisfaction; SWB; subjective wellbeing; mental health